Cancellation Standard of Agreements Based on the Doctrine of Undue Influence in Court Verdicts - A. Budhiawan; T. Kamello; N. N. Sirait; H. Purba (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The doctrine of undue influnce has now become one of the new grounds of will defect to cancel the agreement or contract in the court’s practices. Undue influence as a condition of will defect is not set out in the Civil Code. This study discusses the cancellation standard of the agreement due to a defect of will be based on the doctrine of undue influence in the court judgments. The research method is a normative juridical through several approaches: doctrinal approach and theoretical approach that are associated with secondary data in the form of statutory provisions, and court verdicts relating to the legal problems. The results of the study found that the court verdicts to cancel the agreement based on the doctrine of undue influnce is occurs due to two main factors: the economic excellence factor and the psychiatric excellence factor. Several elements used to see the event are (1) the existence of a special circumstance, (2) a real thing, (3) abuse of circumstance, and (4) causal relationship. It can be concluded that undue influence doctrine is contrary to the principle of justice, the principle of freedom of contract, the principle of consensus, the principle of good faith, as well as the principles of decency and habit. It’s recommended to form a legal norm in the Civil Code. The doctrine of undue influence should also be specified to limited circumstances of pre-contract, after execution of the contract, or because of a real loss for either the involved parties.